Developing Algorithm Based on Activity and Mobility for Pressure Ulcer Risk Among Older Adult Residents: Implications for Evidence‐Based Practice. Issue 2 (9th November 2021) - Avsar, Pinar; Budri, Aglecia; Patton, Declan; Walsh, Simone; Moore, Zena
Abstract: Background: A pressure ulcer (PU) is a localized injury to the skin or underlying tissue usually over a bony prominence. The prevention PU per patient per day is costly; therefore, the detection of a PU at its earliest stage is imperative to afford timely interventions. Currently, there are very few clinically useful tools to assist with early PU detection and prevention. Aim: There were two primary aims of this study: (1) to investigate the relationship between activity, mobility, and PU development; and (2) to ascertain the next steps for delineating an algorithm based on activity and mobility for detecting PU risk among older adult residents in long‐term care. Method: This quantitative, prospective, descriptive, non‐experimental study was conducted between July 2019 and March 2020 among 53 older adult residents who were followed for 4 consecutive days. Participants' Braden score, Elderly Mobility Scale (EMS) score, Movement Level, and 6‐item Cognitive Impairment Test score were assessed. Further, the sacrum and heels were assessed daily using a non‐invasive subepidermal moisture (SEM) scanner and visual skin assessment (VSA). SEM values > 0.5 were considered as indicative of the presence of an SEM‐PU. Results: The incidence rate of VSA‐PU was 15.1% ( N  = 8). There was an incidence of 87.5% ( N  = 42) of SEM‐PU damage. According to the Braden subscale, Mobility Braden, most of the participants (62.2%, N  = 33) were assessed as having no limitations/slightly limited mobility, while the EMS indicated that most of the participants (67.9%, N  = 36) were classed in an independent category. From the 42 SEM‐PUs observed, 62% ( N  = 26) occurred among the low movers, and 38% ( N  = 16) occurred among the high movers. Linking Evidence to Action: Using traditional methods for the assessment of movement does not provide insight into the protective nature of the movement. Given that both low‐ and high‐moving patients can develop tissue damage, it is important to focus on the assessment of movement using more objective measures and algorithms, which enable real‐time assessment of the protective nature of the movement. This would enable development of person‐centered PU prevention strategies to reduce the burden of this significant healthcare problem.